Electron-positron annihilation into heavy leptons at two loops - Roman E. Gerasimov; Petr A. Krachkov; Roman N. Lee (Journal of High Energy Physics)
Abstract We calculate the NNLO QED corrections to the C-even part of differential cross section of e + e − → μ + μ − process. We neglect power corrections in the electron mass and obtain the result in terms of Goncharov’s polylogarithms.